Desa Sioban Kecamatan Sipora Selatan Kabupaten Kepulauan Mentawai Tahun 1999-2018 - Yulisa Teti; Refni Yulia; Zulfa zulfa (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2022)
Sioban village has existed since 1945, when the goverment system  was still in the form of a Nagari, since 1999, Sioban village began to undergo canges, because Mentawai District had separated it self from Padang Pariaman Regency and established its own district, namely the Mentawai Island Regency. The Mentawai Island carry out governance, starting from thr division of the sub-district in 2009 in the Mentawai Islands, including the Sipora sub-district, which is the capital of the Sioban sub-district, which is divided into the North Sipora District and the South Sipora District. Based on the results of research since the establishment of the Mentawai Island District, the aim of which is to get out of its backwardness, has not been seen in Sioban Village, South Sipora Subdistrict, because it is seen from the development of the village, infrastructure and social communities that are still langging behind. You can see that in the village at this time there is no internet network, tlephone network is still difficult. Judging from the original Mentawai traditions, the village community, the village community has no longer been preserving these original traditions since the exixtence of government policies.